RELATIONSHIP BETWEEN NUTRITION STATUS, KNOWLEDGE WITH PHYSICAL ACTIVITY 24 HOUR PREGNANT WOMAN TRIMESTER III IN 5 PUSKESMAS KOTA BENGKULU - Andi Kurniawan (Sriwijaya University Learning and Education International Conference, 2018)
The study entitled Relationship Between Nutrition Status, Knowledge Activity with 24 Hour Physical Activity aims to Analyze the relationship between nutritional status with 24 hour physical activity, analyze the relationship of Knowledge of Activity with 24 Hour Physical Activity and analyze relationship result of Nutrition Status, Knowledge of Physical Activity 24 hours of pregnant women Trimester III at 5 public health centers Bengkulu City. Methods This study used an observational analytic, cross-sectional research design. The sample of this research is pregnant mother of Trimester III which amounted to 107 people with technique of taking sample of consecutive non random sampling. Data were collected by interview using questionnaire and data Card Mother and Child, then tested using Chi Square analysis. There was no relationship between nutritional status (p = 0.432), age (p = 0.941), parity (p = 0.148) and age (p = 0.584) with 24 hour physical activity. However, there is a relationship between knowledge and physical activity 24 hours (p = 0.016). The results of statistical tests showed that nutritional status does not have significant relationship with physical activity 24 hours while knowledge has a significant relationship with physical activity 24 hours. Pregnant women are expected more often to follow integrated service station held at public health centers so that condition of fetus more controlled.